Protein Requirements in the Critically Ill: A Randomized Controlled Trial Using Parenteral Nutrition. (August 2016) - Ferrie, Suzie; Allman-Farinelli, Margaret; Daley, Mark; Smith, Kristine
Background: Current recommendations for higher protein/amino acid provision in the critically ill are based on weak evidence. This double-blinded randomized controlled trial aimed to compare standard amino acid intake with the higher level recommended as the minimum for critically ill patients. Methods: In total, 119 patients requiring parenteral nutrition (PN) in an intensive care unit (ICU) were randomized to receive blinded PN solutions containing amino acids at either 0.8 g/kg or 1.2 g/kg. Primary outcome was handgrip strength at ICU discharge. Secondary outcomes measured at study day 7 included handgrip strength, fatigue score (using the Chalder scale), and ultrasound measurements of muscle thickness at defined body sites. Analysis of covariance was used to control for age, sex, nutrition status (Subjective Global Assessment), Acute Physiology and Chronic Health Evaluation II (APACHE II) score, and baseline measurement. Results: Actual amino acid delivery to the 2 groups was 0.9 and 1.1 g/kg respectively, averaged over the first 7 days. Grip strength at ICU discharge was not significantly different between groups ( P = .054) despite being improved at study day 7 in the group receiving the higher level of amino acids (mean [SD], 22.1 [10.1] vs 18.5 [11.8] kg, P = .025). These patients also had less fatigue (Chalder score, mean [SD], 5.4 [2.2] vs 6.2 [2.2], P = .045) and greater forearm muscle thickness on ultrasound (mean [SD], 3.2 [0.4] vs 2.8 [0.4] cm, P < .0001). Nitrogen balance was significantly better at study day 3 but not at day 7. There was no difference between groups in mortality or length-of-stay measures. Conclusion: The higher level of amino acids was associated with small improvements in a number of different measures, supporting guideline recommendations for ICU patients. This trial was registered at Australian New Zealand Clinical Trials Registry (www.anzctr.org.au ) as ACTRN12609000366257.